Evaluating Sustainable Alternatives for Cocoa Waste Utilization Using the Analytic Hierarchy Process (2024)
Cocoa production has emerged as an effective agricultural strategy to reduce conflict in Colombia, transitioning from coca to cocoa cultivation. While this shift has provided economic benefits, it has also resulted in the generation of substantial cocoa by-products. Although there are various alternative methods of utilizing these by-products, many farmers are unaware of them, and others lack the necessary tools to determine which alternative is the best to pursue. This study sought to explore sustainable options for cocoa waste utilization through the application of the Analytic Hierarchy Process (AHP). By employing technological surveillance, viable options for reusing cocoa residues were identified. The AHP results indicate that pellet production is a promising alternative for rural communities. It is also a potential source of energy that could address the community’s need for alternative energy sources. Initially, other energy production alternatives were not explored. However, in response to the AHP findings, this study also explored the use of cocoa waste combined with animal manure for energy generation through anaerobic digestion.